The Effect of Factor XIII on Wound Granulation in the Rat - Marktl, W; Rudas, B (Thrombosis and Haemostasis, 1974)
The effect of exogenously applied factor XIII on wound healing was studied, using a special wound granulation model. It has been found that great amounts of factor XIII are able to improve the wound granulation. The manner of application, i.e. local or intravenous, seems to be without influence. Possible connections between factor XIII and wound healing are discussed. The reason for the improved wound healing after application of great quantities of factor XIII remains unclarified.